2008
DOI: 10.1007/s00702-008-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Agmatine enhances the anticonvulsant action of phenobarbital and valproate in the mouse maximal electroshock seizure model

Abstract: Accumulating evidence indicates that agmatine (AGM--an endogenous neuromodulator/neurotransmitter in the brain) exerts the anticonvulsant action in various in vivo experiments. Therefore, the aim of this study was to assess the influence of AGM on the protective action of numerous conventional and newer antiepileptic drugs [carbamazepine (CBZ), lamotrigine (LTG), oxcarbazepine (OXC), phenobarbital (PB), phenytoin (PHT), topiramate (TPM) and valproate (VPA)] in the mouse maximal electroshock seizure (MES) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…The results from the present study are in accordance with several previous studies demonstrating that high doses of agmatine had marked anticonvulsive effects (35). In the present study, only rats treated with a high dose of agmatine (40 and 80 mg/kg/d) demonstrated clear inhibitory effects.…”
Section: Discussionsupporting
confidence: 93%
“…The results from the present study are in accordance with several previous studies demonstrating that high doses of agmatine had marked anticonvulsive effects (35). In the present study, only rats treated with a high dose of agmatine (40 and 80 mg/kg/d) demonstrated clear inhibitory effects.…”
Section: Discussionsupporting
confidence: 93%
“…Fresh drug solutions were administered as follows: phenytoin -120 min; phenobarbital -60 min; and valproate and carbamazepine -30 min, before electroconvulsions and brain sampling for the measurement of antiepileptic drug concentrations. The pretreatment times before testing of the antiepileptic drugs were based upon information about their biological activity from literature and our previous experiments [14,17]. Xanthotoxin (Fig.…”
Section: Drugsmentioning
confidence: 99%
“…The threshold for maximal electroconvulsions was recorded for 3 different doses of xanthotoxin: 50, 100 and 150 mg/kg. The experimental procedure has been described in more detail in our earlier studies [13][14][15]17,19]. …”
Section: Maximal Electroshock Seizure Threshold Testmentioning
confidence: 99%
“…In fact, only agmatine and arginine are able to cross the blood-brain barrier [21]. Systemic injection of agmatine has been shown to substantially increase cortical agmatine concentration in rats [22], even though other studies suggest that 99% of the injected agmatine is rapidly metabolized by peripheral tissues [23]. This is interesting as agmatine is believed to function as a CNS neurotransmitter by binding to NMDA receptors [24], as well as acetylcholine, imidazoline, and serotonin receptors [15].…”
Section: -Role Of Polyamines In Cnsmentioning
confidence: 99%